Dynamics of the Inflation-Hedging Capabilities of Real Estate Investment Portfolios in the Nigerian Property Market - Nwosu A.E.; Bello V.A.; Oyetunji A.K.; Amaechi C.V. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
There has been a wide belief that real estate is a source of good investment portfolios because it has a hedge against inflation. Considering this notion, the present research examined the dynamics of the inflation-hedging capabilities of real estate investment in Nigeria?s three foremost property markets, Abuja (Maitama and Central Business District), Lagos (Lekki and Victoria Island), and Port Harcourt (Rumu Ibekwe and Aba Road). To achieve this aim, this study was carried out by exploring the returns on different types of commercial properties in the chosen location and investigating the effect of inflation on such returns in order to come up with the hedging capabilities of the assets. Out of the four property prime locations in Nigeria?s market, these selected study sites were purposely selected for investigation because they comprise the most desirable and preferred properties regarding location, standards, aesthetics, and value. From the data collected, a mean return, coefficient of variation, and ordinary least square regression analysis were completed. In terms of the coefficient of variation (CV), the findings reveal that the duplex in Port Harcourt exhibits the most performed investment, with a value of 0.33, compared to other locations. However, in terms of the expected return (ER), the duplex outperformed other property types in the different locations, with a return of 39.56%. Results also show that inflation has an adverse effect on the returns of the office space for the three locations considered, with the expected returns below 1%. The block of flats in Abuja has a complete defence against the three components of inflation, with a coefficient beta of 0.5633, 0.6586, and 0.8440, respectively. Thus, investors should consider inflation and other investment attributes when making decisions among arrays of investments. This will help guard against the widespread perception that real estate has a hedge against inflation. This paper adds to the existing literature on inflation hedging by investigating the effect of inflation on the real estate investment returns of commercial properties. ? 2023 by the authors.